EFEKTIVITAS CENDAWAN ENTOMOPATOGEN ISOLAT LOKAL TERHADAP HAMA KUMBANG UBI JALAR Cylas formicarius FABRICUS - Nina Jeni Lapinangga; Yosefus F. da Lopez (Politeknik Pertanian Negeri Kupang, 2016)
Sweet potato production is plagued by pests Cylas formicarius Fabricus. These pests can be controlled by using entomopathogenic fungus as a biological control agent. Local biological agents will have a better adaptation and higher performance to control pests compared with biological agents which are introduced from other areas. This study aims to explore the local isolate entomopathogenic fungal species, identify and testing the pathogenicity on C. formicarius. Implementation of the study consists of several stages: collection and maintenance of insects, exploration entomopathogenic fungus, and the effectiveness test of entomopathogenic fungal isolates in the laboratory. The entomopathogenic fungus types which can be found in South Central Timor is Metarhizium anisopliae and Beauveria bassiana. Both of these fungi cause mortality in larvae of C. formicarius respectively by 80.75% (Metarhizium anisopliae) and 80.25% (Beauveria bassiana). Therefore, both types of the fungus should be developed as a biopesticide for controlling pests C. formicarius.Keyword : Metarhizium anisopliae, Beauveria bassiana, Cylas formicarius Directory for female scat lovers. Free scat porn videos at ScatNude scat sex tube. Share your favorite scat video clips for free and get tons more in return! Scat Porn Tube Be careful, as it's going to be fun and messy here. At Scat Porn Nude we love going all filthy and dirty watching horny babe playing with poo and shitting all over the place. In case you share our enthusiasm for scat porn, this place full of best scat sex videos will be your favorite place to be!